Korelasi Keterampilan Guru dalam Pengelolaan Kelas terhadap Keaktifan Peserta Didik di Madrasah Ibtidaiyah - Nuraini Suhud, Afrida; Nisa', Rofiatun (IBTIDA', 2025)
This study focuses on three main aspects: (1) teachers' skills in managing the classroom, (2) the level of student activity, and (3) the relationship between classroom management skills and student activity. The context of this study is at Madrasah Ibtidaiyah Salafiyah Banin Banat Siman Sekaran Lamongan. Classroom management is defined as the teacher's ability to regulate interaction, utilize time effectively, arrange the learning space, and foster positive habits to create a conducive learning environment. Meanwhile, students' engagement level is significantly affected by the teacher's instructional strategies in fostering a learning environment that promotes active student participation. This study adopted a quantitative approach with a correlational design. The research population included all students in grades IV, V, and VI, with a total of 74 subjects. Data were collected using a closed questionnaire instrument that had passed validity and reliability tests. Subsequently, the collected data were analyzed using the Pearson Product Moment correlation technique with the support of the SPSS version 22 program. The results of the study show that teachers' skills in managing the classroom fall into the moderately high category, while student activity is categorized as high. A correlation coefficient of 0.761 was found with a significance value of 0.000 (p < 0.05), indicating a strong and significant relationship between teachers' classroom management skills and student activity. This finding implies the necessity of improving teachers' abilities through continuous training, which is crucial for ensuring effective classroom management while simultaneously encouraging an increase in student activity during the teaching and learning process.